Extreme C-to-A Hypermutation at a Site of Cytosine-N4 Methylation - Joshua L. Cherry (American Society for Microbiology, 2021)
Mutation produces the raw material for adaptive evolution but also imposes a burden because most mutations are deleterious. The rate of mutation at a particular site is affected by a variety of factors.